Cyber Security in Smart Grid Technology: A systematic Review - Fifit Alfiah; Novi Rifkhah Prastiwi (International Institute for Advanced Science & Technology (IIAST), 2022)
A Smart Grid (SG) is an electrical infrastructure that functions similarly to a traditional power grid but includes scalable and ubiquitous two-way communications, timely control capabilities, large-scale integration of dispersed resources, and resource efficiency. Pervasive smart monitoring technologies, autonomous equipment defect detecting, and self-healing are all included in the SG. It is intelligent infrastructure because of features such as 'Wireless Automatic Meter Reading' (WAMR), power system stability monitoring, distributed energy resource optimization, and Demand Response system applications. Given some of these distinguishing characteristics, SGs are without a doubt the world's future power infrastructure. A smart grid may link millions of people and devices in a network, necessitating its robustness, reliability, and security. Because of the long-range communication over open networks, one of the primary issues of today's smart grid systems is security. Cybercriminals, hackers, and terrorists are attempting to assault this national infrastructure in order to obtain control over automated energy monitoring and remote control for personal benefit. This research article provides a full overview of Smart Grids, including their design, methodology, and communication protocols, but the attention is mostly on the cyber-attacks that have been carried out and the remedies that have been advised for smart grids. Finally, we cover the numerous cyber security difficulties, as well as the topics that remain unsolved in the literature and the present solution area, as well as prospective research gaps.